The small molecule drug CBL0137 increases the level of DNA damage and the efficacy of radiotherapy for glioblastoma. (28th February 2021) - Tallman, Miranda M.; Zalenski, Abigail A.; Deighen, Amanda M.; Schrock, Morgan S.; Mortach, Sherry; Grubb, Treg M.; Kastury, Preetham S.; Huntoon, Kristin; Summers, Matthew K.; Venere, Monica
Abstract: Glioblastoma (GBM) is an incurable brain tumor with inevitable recurrence. This is in part due to a highly malignant cancer stem cell (CSC) subpopulation of tumor cells that is particularly resistant to conventional treatments, including radiotherapy. Here we show that CBL0137, a small molecule anti-cancer agent, sensitizes GBM CSCs to radiotherapy. CBL0137 sequesters the FACT (facilitates chromatin transcription) complex to chromatin, resulting in cytotoxicity preferentially within tumor cells. We show that when combined with radiotherapy, CBL0137 inhibited GBM CSC growth and resulted in more DNA damage in the CSCs compared to irradiation or drug alone. Using an in vivo subcutaneous model, we showed that the frequency of GBM CSCs was reduced when tumors were pretreated with CBL0137 and then exposed to irradiation. Survival studies with orthotopic GBM models resulted in significantly extended survival for mice treated with combinatorial therapy. As GBM CSCs contribute to the inevitable recurrence in patients, targeting them is imperative. This work establishes a new treatment paradigm for GBM that sensitizes CSCs to irradiation and may ultimately reduce tumor recurrence.